2016
DOI: 10.1002/2015gb005349
|View full text |Cite
|
Sign up to set email alerts
|

Net community production at Ocean Station Papa observed with nitrate and oxygen sensors on profiling floats

Abstract: Six profiling floats equipped with nitrate and oxygen sensors were deployed at Ocean Station P in the Gulf of Alaska. The resulting six calendar years and 10 float years of nitrate and oxygen data were used to determine an average annual cycle for net community production (NCP) in the top 35 m of the water column. NCP became positive in February as soon as the mixing activity in the surface layer began to weaken, but nearly 3 months before the traditionally defined mixed layer began to shoal from its winter ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(146 citation statements)
references
References 81 publications
7
125
0
Order By: Relevance
“…These results indicate that gas exchange parameterizations not explicitly developed for the coastal ocean may be applicable in such environments. Recent studies have indicated that the parameterization of Liang et al (2013) is also appropriate for simulating O 2 in the northeast Pacific Ocean Plant et al, 2016). All of these studies demonstrate that a parameterization with no bubble flux and too much bubble flux will both result in errors in the calculated air-water flux for low solubility gases.…”
Section: Broader Implicationsmentioning
confidence: 97%
See 4 more Smart Citations
“…These results indicate that gas exchange parameterizations not explicitly developed for the coastal ocean may be applicable in such environments. Recent studies have indicated that the parameterization of Liang et al (2013) is also appropriate for simulating O 2 in the northeast Pacific Ocean Plant et al, 2016). All of these studies demonstrate that a parameterization with no bubble flux and too much bubble flux will both result in errors in the calculated air-water flux for low solubility gases.…”
Section: Broader Implicationsmentioning
confidence: 97%
“…However, many gas exchange parameterizations do not explicitly include a bubblemediated flux and there is currently no consensus on the most accurate parameterization for bubble-mediated exchange (Liang et al, 2013;Emerson and Bushinsky, 2016;Plant et al, 2016). Published parameterizations predict a wide range of magnitudes for both the net bubble-mediated flux and the relative importance of bubbles that completely or partially dissolve for a given wind speed and gas saturation anomaly (Hamme and Emerson, 2006;Stanley et al, 2009b;Nicholson et al, 2011;Liang et al, 2013;Nicholson et al, 2016;Plant et al, 2016). For lower solubility gases, such as O 2 , a significant fraction of the total airwater flux is driven by bubbles, and uncertainties in the parameterization of bubble-mediated exchange directly translate to uncertainties in net community production calculated from O 2 mass balance when simultaneous noble gas measurements are not available (Plant et al, 2016).…”
Section: A New Field-deployable Noble Gas Mass Spectrometer -Chaptermentioning
confidence: 99%
See 3 more Smart Citations